Centralizers on Prime and Semiprime Γ-rings - Kadem, Sameer (Iraqi Journal of Science, 2022)
In this paper, we will generalized some results related to centralizer concept onprime and semiprime Γ-rings of characteristic different from 2 .These resultsrelating to some results concerning left centralizer on Γ-rings.